2022
DOI: 10.1155/2022/7275192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mediterranean Diet Compared with the Low-Fat Diet on Patients with Knee Osteoarthritis: A Randomized Feeding Trial

Abstract: Objectives. Knee osteoarthritis is a common global problem, especially in overweight and obese people. It is not clear that weight loss is a factor for pain reduction in these patients or dietary components are important. Herein, we compared the effects of Mediterranean (MD) and low-fat diet on pain, stiffness, and physical function in patients with knee osteoarthritis. Subjects/Methods. In this randomized feeding trial, 129 patients with knee osteoarthritis were enrolled. Participants were randomly allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 32 publications
(34 reference statements)
0
38
0
Order By: Relevance
“…Diets high in EPA and DHA, such as the Mediterranean diet, also have been associated with improvements of pain in patients with OA. 43 However, other OSs found no significant associations of FAs with incidence of OA. 44,45 The difference in findings between intervention and OSs may suggest that the dose of n-3 PUFAs needed to benefit individuals with OA exceeds the usual intake of n-3 PUFAs consumed without supplementation, especially in participants living in areas who have low intakes of marine foods.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Diets high in EPA and DHA, such as the Mediterranean diet, also have been associated with improvements of pain in patients with OA. 43 However, other OSs found no significant associations of FAs with incidence of OA. 44,45 The difference in findings between intervention and OSs may suggest that the dose of n-3 PUFAs needed to benefit individuals with OA exceeds the usual intake of n-3 PUFAs consumed without supplementation, especially in participants living in areas who have low intakes of marine foods.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that women with more symptomatic OA (ie, more pain) at baseline may have increased consumption of n‐3 PUFA–rich foods in response to symptoms. Diets high in EPA and DHA, such as the Mediterranean diet, also have been associated with improvements of pain in patients with OA 43 . However, other OSs found no significant associations of FAs with incidence of OA 44,45 .…”
Section: Discussionmentioning
confidence: 97%
“…This analysis indicates that the young people with a low adherence show higher emotional role and bodily pain. It has been shown that in populations with osteoarthritis, the Mediterranean diet helps to reduce bodily pain [28]. Furthermore, a reduction in chronic pain has been observed with a high adherence to the Mediterranean diet [29].…”
Section: Discussionmentioning
confidence: 99%
“…High-fat diets, consisting of greater concentrations of trans and saturated fats, have demonstrated increased risk factors and pain in individuals with OA [ 101 ]. Conversely, the Mediterranean diet emphasizes fruit and vegetables, whole grains, and healthy fats (omega-3 sources of olive oil, nuts, fatty fish, and low-fat dairy) and has been shown to reduce the prevalence of OA in some individuals [ 102 ].…”
Section: Supplementationmentioning
confidence: 99%